2017
DOI: 10.1021/acs.chemmater.7b01566
|View full text |Cite
|
Sign up to set email alerts
|

Hierarchical Ga-MFI Catalysts for Propane Dehydrogenation

Abstract: We report the synthesis, characterization, and enhanced propane dehydrogenation properties of hierarchical Ga-MFI zeolite catalysts synthesized by two different methods: (i) repetitive branching and (ii) utilization of a long chain alkyl SDA. Structural, compositional, and morphological characterizations confirm that the Ga-MFI catalyst materials have hierarchical structures including micropores and mesopores in a single particle and show that Si/Ga ratios comparable to bulk Ga-MFI catalysts can be obtained. A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
59
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 86 publications
(68 citation statements)
references
References 43 publications
4
59
0
Order By: Relevance
“…The synthesis of Ga-modified ZSM-5 with hydrothermal crystallization has been reported [ 46 , 54 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 ]. Awate et al reported synthesis of Ga-modified ZSM-5 from sodium gallosilicate gel using triethyl-n-butylammonium bromide as the structure-directing agents (SDA) [ 65 ].…”
Section: Preparation Of Ga-modified Zsm-5mentioning
confidence: 99%
“…The synthesis of Ga-modified ZSM-5 with hydrothermal crystallization has been reported [ 46 , 54 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 ]. Awate et al reported synthesis of Ga-modified ZSM-5 from sodium gallosilicate gel using triethyl-n-butylammonium bromide as the structure-directing agents (SDA) [ 65 ].…”
Section: Preparation Of Ga-modified Zsm-5mentioning
confidence: 99%
“…The hierarchical Ga-MFI catalysts have a higher Lewis acid site with respect to conventional Ga-MFI. For this reason, the hierarchical Ga-MFI catalysts exhibit improved propylene selectivity from 35% to 80% at 600 • C. The higher performance relates to a lower propylene adsorption and the Brønsted and Lewis acid sites distribution around the mesopores [73]. In addition, the Pt silicalite-1 nanosheets exhibit high propylene selectivity around 95% because they can prohibit the side reaction and reduce the diffusion limitation.…”
Section: Catalytic Cracking and Dehydrogenation Of Alkanesmentioning
confidence: 99%
“…Therefore, the development of novel dehydrogenation catalysts is still needed. In recent years, metal oxide‐based catalysts (VO x , MoO x , GaO x , In−Ga−O, Zn−Nb−O), carbon‐based catalysts, metal sulfide‐based catalysts, Sn‐based catalysts and single atom catalysts have been extensively studied. The dehydrogenation performances of these catalysts are summarized in Table .…”
Section: Novel Dehydrogenation Catalystsmentioning
confidence: 99%